ความวิตกกังวลของนิสิตแพทย์ชั้นปีที่ 2 คณะแพทยศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย ปีการศึกษา 2551 - อัมพร ธนะวัฒน์สัจจะเสรี (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Objectives: To study prevalence, level of anxiety and coordinated factors in the second year medical students at Faculty of Medicine, Chulalongkorn University in year course 2008. Methods: Quantitative and qualitative methods on data collection were applied. The State Anxiety Inventory questionnaires were distributed to the second year medical students. According to gender and level of anxiety, students were classified to 4 groups with 7 students in each group. Focus group discussion was done. Data were analyzed by descriptive statistic: frequency, percentage, mean, standard deviation, Chi-Square test and Multiple Linear Regression. Results: majority of the second year medical students are female. Most students got learning motivation by themselves. Their common problems were inability to understand and following the instructors during lecture period. They showed less concern about portfolio collection and class presentation, these problems could be solved by consulting their friends. Although competitive learning atmosphere in the faculty, students helped each other. Most students are satisfied in overall aspects and still willing to continue their learning. According to the qualitative study, the result is found that most students have decided to study in Faculty of Medicine by themselves. Their anxiety was associated with quality and difficulty in studied subjects, examination score, class presentation, portfolio collection including the anxiety produced by the influence of other competitive classmates. From the study of students’ anxiety in past 1 month, the prevalence of medium, low and high level of anxiety is 62.2%, 24.3% and 13.5% respectively. Three factors are statistically related to anxiety are learning problems, class presentation, and overall satisfaction in the Faculty of Medicine (P<0.05). Students without problems in learning and class presentation show more anxiety than the students who had. Students who are satisfied in learning environment showed significantly less anxiety than the students who are not. Therefore it is implied that having anxiety, sometimes can affect as a positive reinforcement. The predictors of anxiety are. Portfolio collection (R² =0.188), motivation to study for good future economic status (R² =0.171), class presentation (R² =0.143) and learning problems (R² =0.099). Conclusion: The prevalence of students’ anxiety is medium. Three factors which related to anxiety are learning problems, class presentation, and overall satisfaction in the Faculty of Medicine.